An Exploratory Study on Subjective Perceptions of Happiness From India - Singh, Kamlesh; Bandyopadhyay, Shilpa; Saxena, Gaurav (Frontiers in Psychology, 2022)
The present study aimed at understanding the subjective perception of happiness in a sample of Indian participants from diverse socio-economic backgrounds. Using convenience sampling, individual interviews were conducted with 60 participants aged between 19 to 73 years (M Age=40 years). This study employed reflexive thematic analysis to analyse the written transcripts. Nine themes were generated which captured the essence of happiness for Indians – Feelings and Expressions of Happiness; Human Ties and Happiness which encompassed four sub-themes - family bond, the company one keeps, the pandemic and social disengagement, and the nation, society and happiness; Satisfaction with Material Needs and Resources; Lifestyle and Health; Work and Play; Accomplishment and Appreciation; Nature Connectedness; Religious and Spiritual beliefs; and Happiness as a Personal responsibility – Role of Positive Personality Traits. These findings revealed our respondent’s multidimensional conceptualization of happiness, and adds to the growing body of happiness literature from the South Asian context.